High-mass loading V3O7·H2O nanoarray for Zn-ion battery : new synthesis and two-stage ion intercalation chemistry - Chen, Duo (2021)
Vanadium-based materials are promising cathode materials for aqueous rechargeable zinc-ion batteries (ZIBs). However, up to now, the detailed Zn ion intercalation mechanisms are still not fully clear. In this work, we first show a new facile synthesis approach for V3O7·H2O nanoarray cathode with large mass loadings (1.0–12 mg cm−2). An empirical model is proposed to assess the utilization ratio of active materials under different mass loadings. Then, through the combination of first-principles calculations and a series of ex-situ characterizations, we identify for the first time a two-step Zn2+ intercalation mechanism in V3O7·H2O. The stepwise and reversible intercalation process is manifested by different diffusion energy barriers and segmented electrochemical kinetics in various discharge depths. The nanoarray binder-free electrode is also applied in pouch cells which show high capacities than state-of-the-art ZIB pouch cells. This study may provide an elucidation for the disputed Zn2+ intercalation chemistry of vanadium-based cathodes in ZIBs as well as a guidance to the design of high-mass-loading battery materials.